The Polymorphism of miR-146a (rs2910164) and Breast Cancer Risk: A Meta-Analysis of 17 Studies - Moossavi, Maryam; Shojaee, Maryam; Musavi, Mahsa; Ibrahimi, Reza; Ibrahimi, Mostafa; Khorasani, Milad (MicroRNA, 2020)
Background: Single-Nucleotide Polymorphisms (SNPs) in genes responsible for coding microRNAs (miRNAs) are shown to be crucial in progression of Breast Cancer (BC). Objective: The purpose of this meta-analysis is to obtain more definitive and reliable results due to the ambiguity and inconsistency of the previous findings in this regard. This study aimed at clarifying the association of mir14a polymorphisms with breast cancer. Methods: We searched PubMed, EMBASE, Web of Science and Google Scholar databases for papers published before August 10, 2019. Afterward, genotypes’ distribution, genotyping methods and ethnicity groups were extracted and Overall analyses were conducted. A total number of seventeen researches on 7676 subjects and 7476 controls were found to meet our criteria in this meta-analysis. Results: Our observations confirmed the increased risk in breast cancer with rs 2910164 polymorphism in three genetic models: allele contrast fixed genetic model, Recessive fixed genetic model and CC vs. GG genetic model (P value 0.0109, 0.0404 and 0.0019, respectively). Conclusion: The rs2910164 polymorphism is associated with increased breast cancer risk. We suggest that more multicenter studies with larger samples investigate this matter to further clarify the association and verify our findings.
Keywords: single-nucleotide polymorphisms